Current aspects of implementing internal quality assurance system at a higher education institution (the experience of Lviv Polytechnic National University) - Kolodii, Ihor; Havran, Maryana (Lviv Politechnic Publishing House, 2017)
The article deals with the experience of implementing internal quality assurance system (IQAS) at Lviv Polytechnic National University. The authors explore the current problems of quality improvement in training specialists at higher schools. The legislative framework of higher education for providing high-quality education and improving the educational process is considered. The authors prove that every higher education institution should use quality management system that cannot be provided without a modern integrated higher education quality assurance system in general and all of its components in particular. They present the modern internal quality assurance system for educational activities and higher education at Lviv Polytechnic National University that allows training competitive specialists in various fields of vocational education. The researchers highlight the conceptual principles of quality assurance for educational activities and higher education at the University. The authors identify procedures and measures for IQAS implementation and University staff and units that are responsible for IQAS organization and effective operation. They define the main functions of the system for monitoring and quality control of the educational process and training specialists, and the main tasks and functions of the Quality Management System Assurance Department of Lviv Polytechnic.
Keywords: quality; quality of education; internal quality assurance system; IQAS; quality management system; quality of educational process outcomes